3D Seismic Density Models of the Earth’s Crust and Structural Diagrams of Tectonic Zoning of the Middle Urals - Byzov, D.D.; Martyshko, P.S.; Ladovskii, I.V.; Tsidaev, A.G. (Russian geology and geophysics, 2024)
—For the territory of the Middle Urals segment, a high-resolution grid density model of the upper part of the lithosphere was constructed (grid step is 500 m) to the depth of 80 km – the first regional level of isostatic compensation. The spatial framework of density sections serves as the basis for a three-dimensional (3D) interpolated density model – an initial approximation model. The corrections to the density model of the initial approximation are found from the solution of the linear inverse gravimetry problem of practically meaningful correctness sets of density equivalents. The fairly thin horizontal layers of the grid density model are selected as such sets. The method and technology to calculate 3D density distribution with reference to 2D data along reference seismic sections are embedded in the methodology for quantitative interpretation of potential fields with the construction of 3D geophysical models. The relief of the internal boundary surfaces of the upper, middle and lower crust is compared to the structural scheme of tectonic zoning along the surface of the basement. To construct tectonic schemes, lithostatic pressure anomalies are also used; they are calculated from a general integral characteristic – the mass of density columns from the Earth’s surface to a given depth. Anomalies of lithostatic pressure for each layer of a 3D grid density model are proportional to excessive density within the layer, so that a density model is easily converted into a lithostatic model. 3D anomalies of lithostatic pressure clearly configure the block structure of the earth’s crust at different depth sections. In the projection at the surface of the middle and lower crust, the contours of lithostatic anomalies correspond to the tectonic zoning scheme of the basement, built based on potential fields. A comparison of ‘block diagrams’ of density and lithostatic models is used to identify structural elements of different order of deep tectonic zoning at different depth sections.